A study on career aspirations and its relationship with the academic performance of undergraduate management students: are they realistic?. (7th May 2021) - Sapra, Jayashree; Chaudhary, Mona; Jeswal, Ruchika
The aim of the study was to explore the career aspirations of 547 university students of undergraduate management program in Delhi and NCR of India so that the future career development activities could be aligned better. In the first phase, the impact of gender behaviour on level and area of career aspiration was studied whereas in the second phase, influencing factors effecting career aspirations of youth were studied. In the third phase of the study, an effort to identify the volume of focus of the students towards entrepreneurship as career choice was done. In the last phase, relationship between level of career aspirations and academic performance of students was studied. Statistical methods like central tendency, correlations, and inferential statistics were used to understand relationships between study variables. There was a minimal positive relationship between career level expectations and student's academic performance. The findings suggest that students have high career ambitions but are not at a reasonable level and also showed relatively low academic performance. Policymakers can develop the policies to create conducive environment for the youth of the country and their aspirations.